Results of quantitative assessment of seaward migrating pink salmon fry in the Malaya Khusi river (north-east of Sakhalin) in 2021 - E. A. Kirillova (Известия ТИНРО, 2022)
Following the results of quantitative assessment in the Malaya Khusi river, total number of seaward migrating pink salmon fry was 0,22 mln. Extremely low number of pink salmon fry is is due to unfavorable environmental conditions during embryonic and larval development. Seaward migration of pink salmon fry started 10 days later relative to the long-term average. Previously, pink salmon alevins, physiologically unprepared for migration to the sea, were washed out of from ground affected by massive flood. The maximum of intensity of migration occurred on June 20–21. Variation in the intensity of migration under stable hydrological conditions was determined by fluctuations in water temperature. Migration of pink salmon took place at the dark time of the day. Average body length and weight of seaward migrating pink salmon fry increased slightly during migration. The proportion of fish with a residual yolk sac varied significantly. By the end of the migration period, individuals which began to feed in fresh water were found among seaward migrating fry.